Assessing spaces in Malay traditional house - Nangkula, Utaberta; Nik Ramzi Shah, Nik Farah Elina; Mohd Rasdi, Mohd Tajuddin; Mohd Yunus, Mohd.Yazid; Ismail, Nor Atiah; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
A Traditional Malay house is a vernacular house improvised from generations to generations by the Malay community and is now outfitted to fill their basic needs, culture and their environment. In the early days, a Malay house is usually called 'rumah asas' or basic house and 'pondok' or a cabin. These simple kind of houses were developed during the rise of implementing traditions before becoming bigger and more complex. This papers tries to describe and architecturally analyse the co-relation between one custom and ritual in Malay culture and how its effect the design of their house. It's expected that this paper can start a further discussion for an architect and practitioners in the housing design in Malaysia to be more sensitive in addressing this cultural issue in their terrace houses design.